Experimental and Numerical Study of Strength and Failure Behavior of Precracked Marble under True Triaxial Compression - Yong Han; Yuemao Zhao; Jinglong Li (Shock and Vibration)
Cracks play an important role in evaluating the strength and failure behavior of engineering rock mass. In order to increase the understanding of strength and failure mechanism of precracked rock, crack propagation and coalescence from preexisting cracks under true triaxial compression are investigated using true triaxial compression tests and Cellular Automata Software for engineering Rockmass fracturing process (CASRock). Three types of specimens were studied experimentally and numerically. Experimental and numerical results show that both the preferential angle and areal intensity of preexisting cracks can affect the compressive strength and failure behavior of the specimens. The peak strength firstly decreases and then increases with increase of the preferential angle. Also, the peak strength nonlinearly decreases with the increase of cracks’ areal intensity. The numerical results show that the crack initiation and coalescence are observed and characterized from the inner and outer tips of preexisting cracks in specimens containing single crack and multiple parallel cracks. The main shear failure in the specimen containing multiple unparallel preexisting cracks initiate and propagate from one of the macroscopic preexisting cracks, and other preexisting cracks do not initiate, propagate, and coalesce until reaching the peak strength.